Stimulating Effect of a Novel Synthesized Sulfonamido-Based Gallate ZXHA-TC on Primary Osteoblasts - Jin, Pan (Yonsei Med J, 2015)
PURPOSE: This study is intended to investigate the effects of plants or plant-derived antioxidants on prevention of osteoporosis through the maintenance of reactive oxygen species (ROS) at a favorable level. MATERIALS AND METHODS: In this study, a novel antioxidant, namely 3,4,5-Trihydroxy-N-[4-(5-hydroxy-6-methoxy-pyrimidin-4-ylsulfamoyl)-phenyl]-benzamide (ZXHA-TC) was synthesized from gallic acid and sulfadimoxine. Its effect on osteoblast metabolism was investigated via the detection of cell proliferation, cell viability, production of ROS, and expression of osteogenic-specific genes including runt-related transcription factor 2 (RUNX2), bone sialoprotein (BSP), osteocalcin (OCN), alpha-1 type I collagen (COL1A1), and osteogenic-related proteins after treatment for 2, 4, and 6 days respectively. RESULTS: The results showed that ZXHA-TC has a stimulating effect on the proliferation and osteogenic differentiation of primary osteoblasts by promoting cell proliferation, cell viability, and the expression of genes BSP and OCN. Productions of bone matrix and mineralization were also increased by ZXHA-TC treatment as a result of up-regulation of COL1A1 and alkaline phosphatase (ALP) at the early stage and down-regulation of both genes subsequently. A range of 6.25×10(-3) µg/mL to 6.25×10(-1) µg/mL is the recommended dose for ZXHA-TC, within which 6.25×10(-2) µg/mL showed the best performance. CONCLUSION: This study may hold promise for the development of a novel agent for the treatment of osteoporosis.